THE SIEMENS’ “GADABAY POSSESSION” IN TRANSCAUCASIA - Nekludov, Evgenij Georgievic (History, Archeology and Ethnography of the Caucasus, 2022)
The article presents the history of the so-called “Gadabay possession”, which was the allotment of public lands and forests to the Gadabay and Kalakend copper smelters in Transcaucasia in the second half of the 19th – early 20th centuries. With its help, one of the largest mining enterprises in the region was organized, which belonged to the famous entrepreneurs of the Prussian origin – the Siemens. Forest allotments were required for the procurement of wood fuel for metallurgical furnaces. Using the example of business correspondence between owners and directors of enterprises with regional and central mining authorities, we demonstrate how the conditions of possession, which form the basis of the relationship between owners and the state, influenced the progressive development of the region’s largest mining enterprise. At a certain stage, the rigid connection of the size of forest allotments to the annual productivity of enterprises began to restrict the growth of production, which, in the context of falling market prices, was the only way for the plants to survive. The severity of the fuel problem, on the one hand, caused difficulties in relations with the regional mining administration and an increase in overhead costs, but on the other hand, it pushed the plant management to introduce the latest methods of copper smelting and the use of fossil fuels. Possessional legal relations turned out to be one of the factors that forced the owners to abandon not only forest allotments, but also the further exploitation of a large industrial business, established by many years of hard work.